2018
DOI: 10.1007/s00530-018-0590-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling user quality of experience from objective and subjective data sets using fuzzy logic

Abstract: One of the paramount research questions in the scientific community today is how to remotely assess user quality of experience (QoE) for a specific service. To this end, various user QoE assessment models have been developed; however, they are mostly based on the data gathered from controlled environment experimentation. The aim of this research was to model user QoE for the User Datagram Protocol-based video streaming service from the results of uncontrolled subjective tests. Specifically, using fuzzy logic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…the videos which surround the viewing angle of a user. The paper represents a) the continuation of our previous work [2,3] where extensive subjective evaluation for video streaming service was conducted and the results were used for modelling the user perception based on a number of objective input parameters, and b) one of the outputs of the Quality of Experience for Virtual Reality Applications (QoE4VR) project [4].…”
Section: Subjective Evaluation Of User Quality Of Experience For Omnimentioning
confidence: 99%
“…the videos which surround the viewing angle of a user. The paper represents a) the continuation of our previous work [2,3] where extensive subjective evaluation for video streaming service was conducted and the results were used for modelling the user perception based on a number of objective input parameters, and b) one of the outputs of the Quality of Experience for Virtual Reality Applications (QoE4VR) project [4].…”
Section: Subjective Evaluation Of User Quality Of Experience For Omnimentioning
confidence: 99%
“…Human perception is influenced by a myriad of factors, including individual preferences, cognitive biases, and contextual conditions, making it highly variable and difficult to model accurately. Additionally, different users may have diverse expectations and sensitivities, leading to variations in perceived quality [7,8]. Even subtle changes in video content, such as frame-rate adjustments or compression rates, can impact user perception [9,10].…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%
“…The main advantage of these types of models, relying solely on objective parameters, is their efficiency and ease of implementation, as they do not require human involvement in the assessment process. However, they may fall short in capturing the subjective and perceptual aspects of user experience, thus failing to meet the essence of the QoE concept [7].…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%
“…It was found that many qualitative, subjective factors that are difficult to measure significantly influence users' opinions about the service. These factors include the social context of service usage, internal user state, and their prior experiences, quality of content, application design, and numerous others [3]. Therefore, a new concept (QoE) was introduced, providing a holistic approach to telecommunication service quality analysis.…”
Section: Introductionmentioning
confidence: 99%